Optimization of Nozzle Parameters by Investigating the Flow Behavior of Molten Steel in the Mold under a High Casting Speed - Qiang Liu; Yizhe Du; Pei Xu; Dengfu Chen; Mujun Long (Metals, 2022)
A reasonable flow field in the continuous casting mold is beneficial to produce high quality billets, and the design of the nozzle parameters of the mold is key to regulating the flow behavior of molten steel. Through combining the numerical simulation and physical experiments and taking SEN immersion depth and inner diameter as indicators, the flow behavior of molten steel in the mold during high-speed casting of a 160 mm × 160 mm billet was investigated in detail, and the nozzle parameters were optimized. The results demonstrate that, compared with the inner diameter of the nozzle, the immersion depth has a significant influence on the impact depth of molten steel. On the premise of ensuring that the velocity distribution of molten steel on the surface of the mold is uniform and the impact range inside is appropriate, the inlet immersion depth after optimization is 100–120 mm and the inner diameter is 40 mm. The corresponding impact depth is 605–665 mm, and the maximum velocity of molten steel on the mold surface is between 0.04 and 0.045 m/s. Additionally, the results of the physical experiment and numerical simulation reveal that the optimized nozzle parameters can adapt well to the continuous casting process with a high casting speed.